2021
DOI: 10.1111/cts.13046
|View full text |Cite
|
Sign up to set email alerts
|

The timing of 30‐month stay expirations and generic entry: A cohort study of first generics, 2013–2020

Abstract: Before the first generic version of a drug can be marketed, patent litigation often occurs. The process begins when generic manufacturers notify the FDA of their intent to market a generic copy of a brand-name drug protected by patents, which they allege to be invalid or not infringed (called a Paragraph IV Certification). Assuming the brand-name manufacturer timely responds with litigation, a 30-month stay period is triggered, which bars the FDA from authorizing generic entry until the stay period expires or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In the case of inhalers, a recent study found that only 13% of brand-name products in that class approved over the past 35 years faced any Paragraph IV certifications, and the median time from brand-name approval to first Paragraph IV certification was 14.5 years . By contrast, among oral small-molecule drugs, the median time from brand-name approval to first Paragraph IV certification was 5.2 years . One hypothesis for this difference is that device patents on drug-device combinations deter generic manufacturers from seeking approval; another related possibility is that proving bioequivalence for drug-device combinations to earn FDA approval may be challenging as compared with oral formulations and thus attracts fewer potential competitors.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of inhalers, a recent study found that only 13% of brand-name products in that class approved over the past 35 years faced any Paragraph IV certifications, and the median time from brand-name approval to first Paragraph IV certification was 14.5 years . By contrast, among oral small-molecule drugs, the median time from brand-name approval to first Paragraph IV certification was 5.2 years . One hypothesis for this difference is that device patents on drug-device combinations deter generic manufacturers from seeking approval; another related possibility is that proving bioequivalence for drug-device combinations to earn FDA approval may be challenging as compared with oral formulations and thus attracts fewer potential competitors.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate the innovator for the loss of market share, the Act introduced a period of 5 years of data exclusivity, which only applies to an NCE like RRx-001 [ 49 ]. In practice, this period may be extended to up to 7.5 years since it is common for the brand name company to file a patent infringement lawsuit against a generic applicant, once it receives notice of an ANDA submission, triggering a 30-month stay, during which time the FDA cannot approve the ANDA so long as the infringement lawsuit is ongoing or resolved in the brand name company’s favor [ 50 ].…”
Section: Exclusivity In the Usmentioning
confidence: 99%
“…22 21 U.S.C. § 355(c)(3)(E)(ii).23Kannappan et al (2021Kannappan et al ( ), pp. 1922Kannappan et al ( -1924 Ibid.25 Directive 2001/83/EC (OJ L 311 p. 67), Art.…”
mentioning
confidence: 99%